Hamiltonian formulation of the metric of Friedmann - Villegas, Fulgencio (2018)
From the cosmological Friedmann model, which has been considered function lapse N(t) and the scaling function a(t), it is determined the scalar curvature of Ricci tensor extrinsic curvature, and from this the total formed by the gravitational Lagrangian Lagrangian and the matter is determined; and from conjugates Finally time, the Hamiltonian of the cosmological model is built.